Importance of cervical length in dysmenorrhoea aetiology. (18th May 2016) - Zebitay, Ali G.; Verit, Fatma F.; Sakar, M. Nafi; Keskin, Seda; Cetin, Orkun; Ulusoy, A. Ibrahim
Abstract : The objective of this prospective case–control study was to determine whether uterine corpus and cervical length measurements have a role in dysmenorrhoea aetiology in virgins. Patients with severe primary dysmenorrhoea with visual analog scale scores of ≥7 composed the dysmenorrhoea group ( n  = 51), while the control group ( n  = 51) was of women with painless menstrual cycles or with mild pain. Longitudinal and transverse axes of the uterine cervix and uterine corpus were measured. Correlation between severity of dysmenorrhoea and uterine cervix and corpus axes was calculated. Longitudinal and transverse axes of uterine cervix as well as uterine cervix volume were significantly higher in the dysmenorrhoea group compared to the controls. There was a significant positive correlation between severity of dysmenorrhoea and the length of cervical longitudinal and transverse axes and uterine cervical volume. Our findings reveal longer cervical length and greater cervical volume in young virgin patients with dysmenorrhoea and severe pain compared to those with no or less pain.